New records of Lepidoptera hostplants from Portugal (Insecta: Lepidoptera) - J. Nunes (SHILAP, 2021)
141 new hostplants are added to 100 Lepidoptera species from mainland Portugal, as result of the author’s fieldwork from 2010 to 2020. The majority of records are consistent with hostplant records from other European countries and confirm the wide range of polyphagy of some species.